Faktor-Faktor yang Mempengaruhi Audit Delay Pada Perusahaan Manufaktur Terdaftar di Bursa Efek Indonesia Tahun 2018-2020 - Faradila Nati; Aspiati A. Samiun; Naswan Hadilia; Sofyan Abas (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2024)
This study aims to determine the effect of profitability, solvency and firm size on audit delay in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020.The type of data used in this research is secondary data. Secondary data is a type of research data obtained by researchers indirectly through intermediary media. Secondary data is generally in the form of evidence, historical records or reports that have been compiled for publication or unpublished (Fanny et al, 2017). Secondary data or quantitative data with data sources from financial statements that have been audited by each manufacturing company listed on the Indonesia Stock Exchange (IDX) which is time series data for the period 2018-2020 obtained from the Indonesia Stock Exchange website. (www.idx.co.id). The results of this study indicate that profitability partially has a negative effect on audit delay, solvency partially affects audit delay, company size partially does not affect audit delay, while profitability, solvency, and company size simultaneously have no effect on audit delay.